Coronavirus Pandemic: Situation in Nigeria - Francis Olawale Abulude; Akinyinka Akinnusotu; Samuel Dare Oluwagbayide; Usha Damodharan; Ifeoluwa Ayodeji Abulude (Indonesian Journal of Medical Sciences and Public Health, 2021)
COVID - 19 is an issue ravaging the whole world. Numerous deaths have been recorded particularly elderly individuals and the most vulnerable. In Nigeria, the case isn't extraordinary. The aim of the study was to quantify the number of cases reported in Nigeria. To this effect, the global literature cited in the Nigeria Centre for Disease Control (NCDC) website, the WHO COVID-19 database, other expert-referred scientific articles, and bibliographic databases were used. The results show that as at the sixteenth of May 2020, 288 new affirmed cases and 3 deaths were recorded in Nigeria. Till date, 5445 cases have been affirmed, 778 cases have been released and 171 deaths have been recorded in 34 states and the Federal Capital Territory, While Lagos State is for the most part influenced with 36 deaths in comparison with the cases revealed by the World Health Organization (4,425,485 cases affirmed, 89,269 new cases and 302,059 deaths). The death rate in Nigeria is about 0.05% of the global deaths. The explanation could be because of high temperature (> 30 oC), the intake of garlic, ginger, honey, and heated water by the individuals, and to stop the spread, the Nigerian government has implemented the utilization of nose cover, social distancing, and semi-lockdown of the towns and urban communities. Like HIV and Laser fever this pandemic will be an issue of the past when the adequate vaccine is made available.